- #1

juice34

EQ A.)D(1/r^2)d/dr(r^2(dC/dr))-kC=0

now how do they get Eq B.

EQ B.) (d^2C/dr^2)+(2/r)(dC/dr)-(kC)/D=0

You are using an out of date browser. It may not display this or other websites correctly.

You should upgrade or use an alternative browser.

You should upgrade or use an alternative browser.

- Thread starter juice34
- Start date

- #1

juice34

EQ A.)D(1/r^2)d/dr(r^2(dC/dr))-kC=0

now how do they get Eq B.

EQ B.) (d^2C/dr^2)+(2/r)(dC/dr)-(kC)/D=0

- #2

HallsofIvy

Science Advisor

Homework Helper

- 41,833

- 963

The derivative of r^2 dC/dr is, by the product rule, [r^2 d(dC/dr)/dr]+ [d(r^2)/dr] dC/dr= r^2 d^2C/dr+ 2r dC/dr. Multiplying that by 1/r^2 gives d^2C/dr^2+ 2/r dC/dr so the equation is the same as D(d^2C/dr^2+ 2/r dC/dr)- kC= 0.

EQ A.)D(1/r^2)d/dr(r^2(dC/dr))-kC=0

now how do they get Eq B.

EQ B.) (d^2C/dr^2)+(2/r)(dC/dr)-(kC)/D=0

Dividing the entire equation by D, then, gives eq. B.

Share: